Histological Identification of Helicobacter pylori: Comparison of staining methods - Sharma R, Pranjal; Kumari MK, Kalpana (International Journal of Medical Research and Review, 2015)
Background: Helicobacter pylori has a high incidence world over and especially in developing countries. It causes many histological derangements apart from causing chronic gastritis. Objectives: The study was done to compare Haematoxylin & Eosin (H&E) and Giemsa with Immunohistochemistry (IHC) for the detection of Helicobacter pylori and to correlate the H. pylori positivity with histological changes. Methods: This was a cross sectional study done, in Department of Pathology, on gastric biopsies, with clinical suspicion of Helicobacter pylori infection, received in the period between Jan 13- Dec 13. Sections were stained with H&E, Giemsa and IHC. Along with detection of the organism associated morphological changes were assessed. The stains were validated using IHC as gold standard. Results: A total of 58 samples were evaluated. Fourteen (24.1%) samples showed positivity with IHC, of which 11(19%) and 9(15.5%) were positive with H&E and Giemsa respectively. H&E had a high false positive rate (19%). Giemsa staining showed less sensitivity (64.28%) compared to H&E (78.57%). Morphological changes were assessed and organisms were noted in 14(25.5%) cases with inflammation, 8(30.8%) cases with activity and 2(28.6%) cases with atrophy. No organisms were seen associated with intestinal metaplasia. Conclusion: Giemsa was not found to be superior to H&E in detecting Helicobacter pylori. Use of IHC not only reduces rate of false positive results, but also diagnosis of any mild infection that is not detected on H&E can be made.